Fiber Bragg Grating Sensor for Cutting Speed Optimization and Burr Reduction in Micro-nano Scratching. (2015) - Mandal, Soumen; Roy, Sritama; Chatterjee, Kalyan; Haldar, Saurav; Vijay, Vijay; Hanumaiah, Naga
Abstract: Patterning a surface by scratching at micro-nano scale requires precise instrumentation strategies for generation of accurate patterns which are used in variety of surfaces ranging from bacteria resistant surfaces to water repellent ones. The scratching action leads to temperature rise of tool tip causing expansion of tool and work surface. This results in positioning inaccuracies and surface defects of the machined work. In this work a fiber Bragg grating sensor (FBG) is used to record the temperature rise at the tool tip under different scratching/cutting speeds. The surface integrity of the patterned work was evaluated after machining using a profilometer. The optimized value of cutting speed for minimum inaccuracy and minimum burr was found using Lagrangian multiplier based technique. This work thus ensures real time control of scratching speed based on tool tip temperature variations only, which finally results in better surface integrity of patterned profile.